1993
DOI: 10.1029/93ja01611
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence generated by a gas of electron acoustic solitons

Abstract: The characteristics of the electrostatic turbulence generated by a gas of electron acoustic solitons are investigated. Electron acoustic solitons are shown to propagate in magnetized plasmas up to about 30 ø off the parallel direction without significant changes in their properties relative to the nonmagnetized case. Using the conservation properties of the Korteweg-deVries equation, the velocity distribution function Of the solitOh gas is calculated in the small-amplitude limit. For low cold to hot electron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
153
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(158 citation statements)
references
References 23 publications
5
153
0
Order By: Relevance
“…The negative potential ESWs have been interpreted in terms of ion solitary waves or solitons (Koskinen et al,904 G. S. Lakhina et al: Study of nonlinear ion-and electron-acoustic waves been commonly interpreted in terms of as Bernstein-GreeneKruskal (BGK) modes (Bernstein et al, 1957;Muschietti et al, 1999;Jovanovic and Shukla, 2000;Chen et al, 2005). Other favorite interpretations for these ESWs are based on the nonlinear evolution of a bump-on-tail instability/electron two stream instability (Omura et al, 1996;Kojima et al, 1997;Goldman et al, 1999), and electron-acoustic solitary waves (Pottelette et al, 1990;Dubouloz et al, 1991Dubouloz et al, , 1993Lakhina, 2001, 2004;Tagare et al, 2004. For a detailed discussion of various models, one can refer to Lakhina et al (2000Lakhina et al ( , 2004.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The negative potential ESWs have been interpreted in terms of ion solitary waves or solitons (Koskinen et al,904 G. S. Lakhina et al: Study of nonlinear ion-and electron-acoustic waves been commonly interpreted in terms of as Bernstein-GreeneKruskal (BGK) modes (Bernstein et al, 1957;Muschietti et al, 1999;Jovanovic and Shukla, 2000;Chen et al, 2005). Other favorite interpretations for these ESWs are based on the nonlinear evolution of a bump-on-tail instability/electron two stream instability (Omura et al, 1996;Kojima et al, 1997;Goldman et al, 1999), and electron-acoustic solitary waves (Pottelette et al, 1990;Dubouloz et al, 1991Dubouloz et al, , 1993Lakhina, 2001, 2004;Tagare et al, 2004. For a detailed discussion of various models, one can refer to Lakhina et al (2000Lakhina et al ( , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear ion-acoustic waves in multi-species plasmas have been studied by several workers (Buti, 1980;Hudson et al, 1983;Qian et al, 1988;Bharutram and Shukla, 1986;Berthomier et al, 1998;Reddy and Lakhina, 1991;Reddy et al, 1992). The electronacoustic waves in multi-species plasmas have been discussed by Watanabe and Tanuti (1977); Gary and Tokar (1985); Hellberg (1985, 2001); Ashour-Abdalla and Okuda (1986); Pottelette et al (1990); Dubouloz et al (1991Dubouloz et al ( , 1993; Berthomier et al (2000Berthomier et al ( , 2003; ; Tagare et al (2004);Cattaert et al (2005), Kakad et al (2007) and Lakhina et al (2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the high frequency extension of BEN in dayside auroral zone could be generated by the electronacoustic solitons passing by the satellite. Later on above study was extended to magnetized plasma to explain the turbulence generated by the gas of electron-acoustic solitons (Dubouloz et al, 1993) in dayside auroral zone. Mace et al (1991) studied the arbitrary amplitude electron-acoustic solitons in a two electron component plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Dubouloz et al (1991aDubouloz et al ( , 1993 studied the electron-acoustic solitons (EAS) with two electroncomponents (cold and hot) and motionless ions, and showed that the high-frequency broad band electrostatic noise in the dayside auroral zone can be generated by the EAS. The effect of upward propagating electron beams that are commonly observed in the dayside auroral zone was not taken into consideration.…”
Section: Electron Acoustic Solitonsmentioning
confidence: 99%